Analysis of One Bay Residential Building with Combined RCC Frame and Load Bearing Wall Structures - Maharjan, Rajib; Shrestha, Vivek (Journal of the Institute of Engineering, 2018)
The major purpose of this study is to justify construction method of a hybrid structure in core area with construction complexity due unsafe excavation conditions and tries to define its rigidity and strength. Both RCC and Frame structure transfer same load to ground through foundation but the transfer mechanism varies. In some practical condition, building construction should be carried out in compact areas with unsafe adjoining building where adequate excavation for foundation cannot be carried out. In such cases, one bay hybrid structure is proposed for construction with combined RCC frame structure and load bearing walls. In these combined cases, both structures works as same unit to transfer building load but the transfer pattern varies. The variable load transfer pattern is due to discontinuity in structural system which also effect on seismic response of the building. The placement of a masonry load bearing structure in RCC frame structure varies design of all structural components of the building. To study actual behavior of hybrid structure in various load condition and introducing cost minimization techniques of buildings structural analysis was carried using ETABS 2016 with composite structural arrangement and with induction of load bearing wall as structural component. By which seismic behavior of building in both cases was obtained as well as reduction in rebar percentage and dimensional reduction of structural components can be achieved. Journal of the Institute of Engineering, 2017, 13(1): 117-124